Sample characterization methods

By analyzing the zero loss spectrum and true thickness of the first electron energy loss spectrum of the target layer of the sample, the average free path of the ONO stack structure was calculated, which solved the problem of difficulty in characterizing element content and improved the performance of the chip.

CN114923938BActive Publication Date: 2025-04-29YANGTZE MEMORY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210571405.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-24
Publication Date
2025-04-29
Estimated Expiration
2042-05-24

AI Technical Summary

Technical Problem

In 3D NAND large-scale integrated circuits, especially in the array area, it is difficult to accurately characterize the element content in the ONO stack structure, affecting the programming, storage and reading capabilities of the chip.

Method used

The relative thickness of the target layer is obtained by the zero loss spectrum of the first electron energy loss spectrum of the sample target layer, and the average free path is calculated in combination with the true thickness, providing material atomic density analysis information in another dimension.

Benefits of technology

It realizes the accurate characterization of element content in the ONO stack structure, provides more accurate data support, and improves the programming, storage and reading capabilities of the chip.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Disclosed is a method for characterizing a sample, comprising: performing electron energy loss spectrum analysis on the sample to obtain a first electron energy loss spectrum of the target layer; obtaining the relative thickness of the sample target layer according to the zero-loss spectrum of the first electron energy loss spectrum; slicing the sample in the X direction to obtain the true thickness of the sample; and calculating the mean free path according to the relative thickness and true thickness of the sample target layer. The method for characterizing a sample of the present application obtains the mean free path of the sample target layer through the zero-loss spectrum of the first electron energy loss spectrum of the sample target layer and the true thickness of the sample, and then obtains other characterization parameters of the sample target layer according to the mean free path.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of material testing, and in particular to a method for characterizing a sample. Background Art

[0002] When a high-speed electron beam passes through a material, they collide, which may change the direction of their motion. Therefore, the average distance between these collisions (mean free path) can be used as a measure of their probability of interaction. This distance is usually called the mean free path λ, which is inversely proportional to the scattering cross section and density of the material, that is, λ∝1 / ρnσ, where ρn and σ represent the number density of the medium and the cross section of the particles in the medium. Therefore, changes in the density of the material can be reflected by the mean free path of the material and are crucial for quantitative analysis of the results obtained with various electron spectroscopy.

[0003] In 3D NAND large-scale integrated circuits, especially in the array area, changes in the composition and thickness of core structures such as ONO stack (SiOx-SiOxNx-SiOxNy) significantly affect the programming, storage and reading capabilities of the chip. Therefore, it is crucial to accurately characterize the element content in the ONO stack structure. Therefore, obtaining the true thickness of the material helps to guide accurate quantitative analysis, and obtaining the true mean free path of the material is of great significance for the subsequent characterization of the atomic density of the material. Summary of the invention

[0004] In view of the above problems, the purpose of this application is to provide a sample characterization method, which obtains the relative thickness of the target layer, as well as the relative thickness and true thickness of the target layer through the zero-loss spectrum of the first electron energy loss spectrum of the sample target layer, and obtains the mean free path of the target layer, providing another dimension of information for the analysis of the atomic density of the material.

[0005] According to one aspect of the present application, a method for characterizing a sample is provided, wherein the sample includes a target layer, and the sample surface is a first direction, and is characterized in that the method for characterizing the sample includes: performing electron energy loss spectrum analysis on the sample via the sample surface to obtain a first electron energy loss spectrum of the target layer; obtaining a relative thickness of the target layer of the sample according to a zero-loss spectrum of the first electron energy loss spectrum; slicing the sample in a second or third direction to obtain a true thickness of the sample, the second direction and the third direction being perpendicular to the first direction in pairs; and calculating a mean free path according to the relative thickness and true thickness of the target layer of the sample.

[0006] Optionally, the zero-loss spectrum of the first electron energy loss spectrum is:

[0007] P0=I t / I0,

[0008] Where I0 is the intensity of the zero peak in the first electron energy loss spectrum, I t It's full spectrum strength.

[0009] Optionally, in the step of obtaining the relative thickness of the sample target layer according to the zero-loss spectrum of the first electron energy loss spectrum, the relative thickness of the sample target layer is

[0010] t / λ=ln(It / I0).

[0011] Optionally, in the step of calculating the mean free path according to the relative thickness and the true thickness of the sample target layer, the mean free path of the sample target layer is:

[0012] λ 目标 = Actual thickness / relative thickness.

[0013] Optionally, a focused ion beam is used to slice the sample in a second or third direction.

[0014] Optionally, the sample further includes at least one non-target layer, and the target layer and the non-target layer are made of different materials.

[0015] Optionally, the step of performing electron energy loss spectrum analysis on the sample further includes: obtaining a second electron energy loss spectrum of the non-target layer.

[0016] Optionally, between the step of obtaining the relative thickness of the target layer of the sample according to the zero-loss spectrum of the first electron energy loss spectrum and the step of slicing the sample in the second or third direction to obtain the true thickness of the sample, it also includes: obtaining the relative thickness of the non-target layer of the sample according to the zero-loss spectrum of the second electron energy loss spectrum; obtaining the mean free path of the non-target layer by looking up a table; and obtaining the relative mean free path of the target layer according to the relative thickness and mean free path of the non-target layer and the relative thickness of the target layer.

[0017] Optionally, the relative mean free path of the target layer is obtained according to the relative thickness and mean free path of the non-target layer and the relative thickness of the target layer:

[0018]

[0019] The sample characterization method provided in the present application obtains the relative thickness of the sample target layer through the first electron energy loss spectrum, and obtains the true thickness of the sample target layer through the second or third direction slice according to the focused ion beam, providing more accurate data support for subsequent sample thickness control and quantitative analysis. Furthermore, the mean free path of the sample target layer can be calculated based on the relative thickness and true thickness of the target layer, providing solid data support for the subsequent characterization of the sample target layer and process optimization.

[0020] The sample characterization method provided in this application can obtain the atomic density change and thickness information of the sample target layer by obtaining the mean free path of the sample target layer, which is of great significance for the subsequent material characterization. At the same time, more characterization parameters can be obtained through fewer test and analysis methods.

[0021] In another embodiment, the mean free path of the non-target layer of the sample is obtained by looking up a table, and then the relative thickness of the non-target layer is obtained by the second electron energy loss spectrum, and the relative mean free path of the target layer is calculated according to the mean free path and relative thickness of the non-target layer and the relative thickness of the target layer. When the mean free path of the non-target layer is relatively stable, the relative mean free path has a smaller error than the true mean free path, so that the mean free path of the target layer can also be obtained in samples that are not convenient to slice to obtain the true thickness. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The above and other objects, features and advantages of the present application will become more apparent through the following description of the embodiments of the present application with reference to the accompanying drawings, in which:

[0023] Figure 1 shows a schematic diagram of a molecular mean free path according to some embodiments;

[0024] Figure 2 A flow chart showing a method for characterizing a sample according to a first embodiment of the present application is shown;

[0025] Figure 3a to Figure 3d The FIB image and TEM image of the flat-polished channel hole in the first direction according to the first embodiment of the present application, and the FIB image and TEM image of the flat-polished channel hole after slicing in the second direction are shown in sequence;

[0026] Figure 4a and Figure 4b A schematic diagram of a flat-polished channel hole according to a first embodiment of the present application and a second direction slice diagram of the flat-polished channel hole are shown;

[0027] Figure 5 A flow chart showing a method for characterizing a sample according to a second embodiment of the present application is shown;

[0028] Figure 6 A flow chart showing a method for characterizing a sample according to a third embodiment of the present application is shown;

[0029] Figures 7a to 7d The FIB image and TEM image of the silicon nitride blank slice sliced ​​in the second direction according to the third embodiment of the present application, and the FIB image and TEM image of the silicon nitride blank slice sliced ​​in the third direction are shown in sequence;

[0030] Figures 8a to 8dThe EELS energy low-loss spectrum of a blank silicon nitride slice sliced ​​in the second direction according to the third embodiment of the present application, the TEM image of the blank silicon nitride slice, and the silicon substrate image are sequentially shown;

[0031] Figures 9a to 9e The EELS ADF diagram of the silicon nitride blank wafer according to the fourth embodiment of the present application, the N signal mapping diagram, the N signal density distribution diagram, the ADF diagram of the 3D sample, and the PPSIN obtained by EELS of the 3D sample are shown in sequence. DETAILED DESCRIPTION

[0032] The present application will be described in more detail below with reference to the accompanying drawings. In each of the drawings, the same elements are represented by similar reference numerals. For the sake of clarity, the various parts in the drawings are not drawn to scale. In addition, some well-known parts may not be shown. For the sake of simplicity, the semiconductor structure obtained after several steps can be described in one figure.

[0033] It should be understood that when describing the structure of a device, when a layer or a region is referred to as being "on" or "over" another layer or another region, it may mean that it is directly on the other layer or another region, or that other layers or regions are included between it and the other layer or another region. Furthermore, if the device is turned over, the layer or a region will be "below" or "beneath" another layer or another region.

[0034] If it is intended to describe a situation where it is directly on another layer or another area, this article will use the expression “directly on…” or “on… and adjacent to…”.

[0035] The specific implementation of the present application is further described in detail below in conjunction with the drawings and examples.

[0036] Figure 1 A schematic diagram of the molecular mean free path according to one embodiment is shown.

[0037] When particles moving at high speeds pass through a material, they collide, which may change the direction of their motion. Therefore, the average distance between these collisions is a measure of the probability of a particular interaction. This distance is usually called the mean free path λ, which is inversely proportional to the cross-section and density of the material, that is, λm is proportional to 1 / ρnσ, where ρn and σ represent the number density of the medium and the cross-section of the particles in that medium.

[0038] When the sample is very thin, the average distance that the electrons travel between two scatterings during the interaction between electrons and atoms is the mean free path λ, which can reflect the density of the material to a certain extent. Therefore, how to obtain the mean free path of the material is a problem to be solved.

[0039] Previously, quantitative analysis based on EELS had very strict requirements on sample thickness, generally controlling the relative thickness t / λ at 0.4-0.6, but there has been no definite method to confirm whether there is a gap between the relative thickness information provided by EELS and the true thickness. Therefore, obtaining the true thickness of the material can help guide accurate quantitative analysis and obtain the true mean free path of the material, which is of great significance for the subsequent characterization of the atomic density of the material.

[0040] Figure 2 A flow chart showing a method for characterizing a sample according to a first embodiment of the present application is shown; Figure 3a to Figure 3d The FIB image and TEM image of the flat-polished channel hole according to the first embodiment of the present application, and the FIB image and TEM image of the flat-polished channel hole after being sliced ​​in the X direction are shown in sequence; Figure 4a and Figure 4b A schematic diagram of a flat-polished channel hole according to a first embodiment of the present application and an X-direction slice diagram of the flat-polished channel hole are shown.

[0041] The characterization method of the sample of the present application can be applied to all materials to calculate their mean free path. In the 3D NAND array area, nitride is one of the cores of the storage unit, and its internal defect state has a significant impact on the ability to capture charge. In this embodiment, the channel column of the 3D NAND arrary area is used as an example to illustrate, specifically, to obtain the molecular mean free path of nitride in the channel column.

[0042] Step S01: Perform EELS analysis on the sample to obtain a first electron energy loss spectrum of the target layer.

[0043] Electron Energy Loss Spectroscopy (EELS) utilizes the inelastic scattering of an incident electron beam in a sample. The energy DE of electron loss directly reflects the scattering mechanism, the chemical composition of the sample, the thickness and other information. It can therefore analyze the elemental composition, chemical bonds and electronic structure of a thin sample micro-area.

[0044] In this step, by selecting a uniform and appropriate electron beam current density (200 kV, spot size 5, camera length 38, C2 50, current 0.2 nA), EELS energy resolution and test conditions (1.5 dispersion, 500 eV, 0.01 s), low-loss spectrum information including the relative thickness of the sample can be obtained.

[0045] In this embodiment, the sample is, for example, a channel hole sample polished along a first direction, such as Figure 4aAs shown, the sample includes a target layer and at least one non-target layer, the target layer is the material layer for which the mean free path is to be obtained, and the target layer and the non-target layer are made of different materials. When performing EELS analysis on the sample, the first electron energy loss spectrum of the target layer in the sample can be obtained.

[0046] In this step, an electron beam with known kinetic energy is incident into the sample along the surface of the sample, with the surface of the sample being the first direction. Some electrons interact with atoms and undergo inelastic scattering, losing some energy and making random small deflections on the path. The amount of energy loss in this process is measured by an electron energy spectrometer and analyzed and interpreted. By studying the energy loss distribution of inelastically scattered electrons, the spatial environment information of electrons in atoms can be obtained, thereby studying the various physical and chemical properties of the sample.

[0047] In this embodiment, after performing EELS analysis on the sample, it can be found that the probability of the number of inelastic collisions between the incident electron and the sample material conforms to the Poisson distribution, and the first electron energy loss spectrum satisfies:

[0048] P n =1 / n! (t / λ) n exp (-t / λ) (1)

[0049] Where t is the sample thickness, λ is the mean free path of the sample target layer, and t / λ is the relative thickness of the sample target layer, which can also be called the number of collisions between the incident electron and the sample target layer per unit time.

[0050] Step S02: Obtain the relative thickness (t / λ) of the sample target layer according to the zero-loss spectrum of the first electron energy loss spectrum 目标层 .

[0051] The electron loss spectrum includes rich information about inelastic scattering caused by the interaction between electrons and atoms, and can be mainly divided into three parts: ① zero-loss peak (ZLP): electrons that are not scattered, electrons that are only elastically scattered, or electrons that are inelastically scattered with very little energy loss (such as phonon scattering); ② low-energy loss region: energy loss is less than 50eV, such as plasma resonance, Cherenkov radiation, and inter-band transitions; ③ high-energy loss region: absorption edges (Core-loss edges), near edge fine structure, and extended energy loss fine structure caused by interaction with inner-layer electrons. The zero-loss spectrum is the zero-loss peak in the electron energy loss spectrum. In this embodiment, for example, the electron energy loss spectrum when there is no elastic collision between the incident electron and the sample target layer is considered to be the zero-loss spectrum.

[0052] In this embodiment, according to the probability of the number of inelastic collisions between the incident electron and the sample target layer conforming to the Poisson distribution, it can be known that when the probability that the incident electron does not have an inelastic collision with the sample target layer is when n=0, at this time,

[0053] P n=0 =exp (-t / λ) (2)

[0054] According to the zero-loss spectrum in the first electron energy loss spectrum

[0055] P0=I t / I0 (3),

[0056] Where I0 is the intensity of the zero peak in the first electron energy loss spectrum, I t is the intensity of the full spectrum. After EELS analysis of the sample target layer, the first electron energy loss spectrum can be obtained, and I0 and I t , that is, I0 and I t is a known value.

[0057] Furthermore, according to formula (2) and formula (3), the relative thickness of the sample target layer (t / λ) can be obtained: 目标层 .

[0058] Step S03: Slice the sample in the second direction to obtain the true thickness THK of the sample.

[0059] In this step, the sample is sliced ​​in the second direction, i.e., the X direction, using a focused ion beam (FIB) to obtain the true thickness THK of the sample, and then the true mean free path λ of the sample can be calculated based on the true thickness and relative thickness of the sample. Figure 4b As shown, Figure 4a The second direction (X direction) of the flat-cast channel hole in FIG. The second direction is perpendicular to Figure 4a The first direction shown in FIG. 1 is the direction of the flat-planed channel hole surface.

[0060] Step S04: Calculate the mean free path according to the relative thickness and true thickness of the target layer of the sample.

[0061] In this step, the relative thickness of the target layer of the sample (t / λ) 目标层 And the true thickness THK, the mean free path λ of the sample target layer can be calculated using the following formula:

[0062]

[0063] In this formula, the true thickness of the sample target layer is the true thickness of the sample THK, divided by the relative thickness of the sample target layer (t / λ) 目标层 That is, the true mean free path λ of the sample target layer can be obtained.

[0064] In this embodiment, the mean free path of the sample target layer can at least reflect the material density of the target layer. In other embodiments, the true thickness of the same material layer can be obtained by summing the electron energy loss spectrum and the mean free path.

[0065] Figure 5 A flow chart of a method for characterizing a sample according to a second embodiment of the present application is shown. Compared with the first embodiment, the second embodiment further includes calculating the relative mean free path of the target layer. The same steps as those in the first embodiment are not repeated here, and only the differences are described. The method includes the following steps.

[0066] Step S11: Perform EELS analysis on the sample to obtain a first electron energy loss spectrum of the target layer and a second electron energy loss spectrum of the non-target layer.

[0067] In this step, since the material of the non-target layer is different from that of the target layer, the second electron energy loss spectrum of the non-target layer also conforms to the Poisson distribution, but its specific value is different from that of the first electron energy loss spectrum.

[0068] Step S12: Obtaining the relative thickness of the sample target layer according to the zero-loss spectrum of the first electron energy loss spectrum.

[0069] Step S13: Obtain the relative thickness of the non-target layer of the sample according to the zero-loss spectrum of the second electron energy loss spectrum.

[0070] The steps to obtain the relative thickness of the target layer are the same as those to obtain the relative thickness of the non-target layer (t / λ). 非目标层 When the relative thickness of the non-target layer is calculated based on the zero-loss spectrum of the second electron energy loss spectrum, that is, the intensity of the zero peak in the second electron energy loss spectrum and the intensity of the full spectrum (t / λ), 非目标层 .

[0071] Step S14: Look up the table to obtain the mean free path of the non-target layer.

[0072] In this step, the non-target layer is, for example, an oxide layer, and the mean free path λ of the oxide can be obtained by looking up the table. oxide .

[0073] Step S15: Obtaining the relative mean free path of the target layer according to the mean free path and relative thickness of the non-target layer and the relative thickness of the target layer.

[0074] In this step, since the sample is a sliced ​​sample, it is assumed that the true thickness THK of the target layer and the non-target layer is the same, so the true thickness of the sample can be obtained according to the mean free path and relative thickness of the non-target layer, and the mean free path of the target layer can be obtained according to the thickness of the sample and the relative thickness of the target layer, that is,

[0075]

[0076] However, in this step, the true thickness obtained based on the mean free path and relative thickness of the non-target layer is not obtained by actual measurement, so there is a certain error, resulting in the final mean free path of the target layer being the relative mean free path, which has a certain error from the true mean free path.

[0077] However, when the mean free path of the non-target layer is relatively stable, the error between the relative mean free path of the target layer and the true mean free path is small. At the same time, this method can also be used to measure the mean free path of some samples that are not convenient to slice to obtain the true thickness.

[0078] In this embodiment, if the error between the calculated mean free path of the target layer and the actual mean free path is within the allowable range, it can also be seen from another aspect that λ oxide This is close to the theoretical value, which illustrates the reliability of this method and also proves the stability of block oxide materials from another dimension.

[0079] Step S16: Perform X-slicing on the sample to obtain the true thickness THK of the sample.

[0080] Step S17: Calculate the mean free path according to the relative thickness and true thickness of the target layer of the sample.

[0081] Steps S16 and S17 in the second embodiment are the same as steps S03 and S04 in the first embodiment, so the mean free path of the target layer of the sample can be calculated by referring to the above steps.

[0082] exist Figure 5 In the second embodiment shown, step S16 and step S17 may also be removed.

[0083] In the embodiments of the present application, according to the calculation of the mean free path of nitride in the above two embodiments, we can know that the characterization method of the sample of the present application can calculate the real mean free path and relative mean free path of the sample with little error, or the characterization method of the sample of the present application can at least obtain the relative thickness (t / λ) of the sample material. According to the relative thickness (t / λ) of the sample, the mean free path of the sample, the sample thickness and other characterization information about the sample such as the material density of the sample can be further calculated.

[0084] Figure 6 A flow chart showing a method for characterizing a sample according to a third embodiment of the present application is shown; Figures 7a to 7d The FIB image and TEM image of the second direction of the silicon nitride blank according to the third embodiment of the present application, and the FIB image and TEM image after slicing the silicon nitride blank in the third direction are shown in sequence;

[0085] Figures 8a to 8d An EELS energy low-loss spectrum of a blank silicon nitride wafer, a TEM image of a blank silicon nitride wafer, and a silicon substrate image are shown in sequence according to the third embodiment of the present application.

[0086] Compared with the sample characterization method of the first embodiment, the difference of the third embodiment is that the material selection of the sample is different, and the direction of cutting and analyzing the sample is different. The sample characterization method of the third embodiment will be briefly described below.

[0087] Step S21: Perform EELS analysis on the sample to obtain a first electron energy loss spectrum of the target layer.

[0088] In this embodiment, the sample is a blank silicon nitride wafer (SiN) cut in the second direction (X direction), that is, in this embodiment, the target layer is the substrate Si

[110] layer.

[0089] Electron Energy Loss Spectroscopy (EELS) utilizes the inelastic scattering of an incident electron beam in a sample. The energy DE of electron loss directly reflects the scattering mechanism, the chemical composition of the sample, the thickness and other information. It can therefore analyze the elemental composition, chemical bonds and electronic structure of a thin sample micro-area.

[0090] In this step, by selecting a uniform and appropriate electron beam current density (200 kV, spot size 5, camera length 38, C2 50, current 0.2 nA), EELS energy resolution and test conditions (1.5 dispersion, 500 eV, 0.01 s), low-loss spectrum information including the relative thickness of the sample can be obtained.

[0091] In this embodiment, the sample is, for example, a blank silicon nitride wafer sample cut along the second direction. Figure 7a and Figure 7b As shown, the sample includes a target layer Si

[110] layer, which is a material layer for which the mean free path is to be obtained. When performing EELS analysis on the sample, the first electron energy loss spectrum of the target layer in the sample can be obtained.

[0092] Among them, after EELS analysis of the sample, it can be found that the probability of the number of inelastic collisions between the incident electron and the sample material conforms to the Poisson distribution, and the first electron energy loss spectrum satisfies:

[0093] P n =1 / n! (t / λ) n exp (-t / λ) (1)

[0094] Where t is the sample thickness, λ is the mean free path of the sample target layer, and t / λ is the relative thickness of the sample target layer, which can also be called the number of collisions between the incident electron and the sample target layer per unit time.

[0095] Step S22: Obtain the relative thickness (t / λ) of the sample target layer according to the zero-loss spectrum of the first electron energy loss spectrum 目标层 .

[0096] According to the probability of the number of inelastic collisions between the incident electron and the sample target layer conforming to the Poisson distribution, it can be known that when the probability of no inelastic collision between the incident electron and the sample target layer is n = 0, at this time,

[0097] P n=0 =exp (-t / λ) (2)

[0098] According to the zero-loss spectrum in the first electron energy loss spectrum

[0099] P0=I t / I0 (3),

[0100] Where I0 is the intensity of the zero peak in the first electron energy loss spectrum, I t is the intensity of the full spectrum. After EELS analysis of the sample target layer, the first electron energy loss spectrum can be obtained, and I0 and I t , that is, I0 and I t is a known value.

[0101] Furthermore, according to formula (2) and formula (3), the relative thickness of the sample target layer (t / λ) can be obtained: 目标层 .

[0102] Step S23: Slice the sample in the third direction to obtain the true thickness THK of the sample.

[0103] In this step, the sample is sliced ​​in the third direction, i.e., the Y direction, using a focused ion beam (FIB) to obtain the true thickness THK of the sample, and then the true mean free path λ of the sample can be calculated based on the true thickness and relative thickness of the sample. Figure 7band Figure 7c As shown, Figure 7a and Figure 7b The FIB image and TEM image of the slice image of the third direction (Y direction) of the silicon nitride blank in FIG. Among them, the first direction, the second direction and the third direction are perpendicular to each other.

[0104] Step S44: Calculate the mean free path according to the relative thickness and true thickness of the target layer of the sample.

[0105] In this step, the relative thickness of the target layer of the sample (t / λ) 目标层 And the true thickness THK, the mean free path λ of the sample target layer can be calculated using the following formula:

[0106]

[0107] In this formula, the true thickness of the sample target layer is the true thickness of the sample THK, divided by the relative thickness of the sample target layer (t / λ) 目标层 That is, the true mean free path λ of the sample target layer can be obtained.

[0108] In this embodiment, since the sample is a blank silicon nitride sheet, the target layer is the Si

[110] layer, wherein the relative thickness (t / λ) of the target layer (Si

[110] ) is calculated based on the energy loss spectrum: 目标层 The difference between the real mean free path calculated by the real thickness THK and the theoretical value of the mean free path of Si

[110] obtained by looking up the table is very small and within the allowable error range, that is, the error between the real mean free path calculated and the theoretical mean free path obtained by looking up the table is not large. This also proves the accuracy of using Si

[110] substrate as EELS thickness control, which is of great significance for our subsequent characterization of sample thickness, atomic density and other information.

[0109] Figures 9a to 9e The EELS ADF diagram of the silicon nitride blank wafer according to the fourth embodiment of the present application, the N signal mapping diagram, the N signal density distribution diagram, the ADF diagram of the 3D sample, and the PPSIN obtained by EELS of the 3D sample are shown in sequence.

[0110] Compared with the first and third embodiments, the fourth embodiment uses other materials as the target layer, wherein the sample in the fourth embodiment at least includes a first target layer PPSiN layer (pulsed plasma silicon nitride layer) and a second target layer SiN layer. The same method flow will not be repeated here, and only the calculation process of the mean free path of the corresponding material after using different materials is described.

[0111] EELS analysis was performed on the blank silicon nitride wafer sample to obtain a first electron energy loss spectrum of the first target layer PPSiN layer and a second electron energy loss spectrum of the second target layer SiN layer.

[0112] In this embodiment, the relative thickness (t / λ) of the first target layer PPSiN layer of the sample is obtained according to the zero-loss spectrum of the first electron energy loss spectrum. 目标层1 , the relative thickness of the second target layer SiN layer of the sample is obtained according to the zero-loss spectrum of the second electron energy loss spectrum (t / λ) 目标层2 , slice the sample in the corresponding direction to obtain the actual thickness THK1 and THK2 of the target layer in the sample, and according to formula (4) in the above embodiment, the mean free path λ1 of the first target layer PPSiN layer and the mean free path λ2 of the second target layer SiN layer can be obtained respectively.

[0113] In this embodiment, the mean free path λ1 of the first target layer PPSiN layer and the mean free path λ2 of the second target layer SiN layer obtained according to the formula are not much different from the theoretical values.

[0114] In the present application, based on the calculation of the mean free path of multiple materials in the above four embodiments, we can know that the sample characterization method of the present application can calculate the true mean free path and relative mean free path of the sample with a small error, or the sample characterization method of the present application can at least obtain the relative thickness (t / λ) of the sample material.

[0115] Furthermore, the true mean free path of the sample can be obtained based on the relative thickness of the sample (t / λ) and the true thickness of the sample; the true thickness of the sample can be obtained based on the relative thickness of the sample (t / λ) and the theoretical mean free path of the sample.

[0116] Therefore, according to the relative thickness (t / λ) of the sample, the mean free path of the sample, the sample thickness and other characterization information about the sample, such as the material density of the sample, can be further calculated.

[0117] The sample characterization method provided in the present application obtains the relative thickness of the sample target layer through the first electron energy loss spectrum, and obtains the true thickness of the sample target layer through the second or third direction slice according to the focused ion beam, providing more accurate data support for subsequent sample thickness control and quantitative analysis. Furthermore, the mean free path of the sample target layer can be calculated based on the relative thickness and true thickness of the target layer, providing solid data support for the subsequent characterization of the sample target layer and process optimization.

[0118] The sample characterization method provided in this application can obtain the atomic density change and thickness information of the sample target layer by obtaining the mean free path of the sample target layer, which is of great significance for the subsequent material characterization. At the same time, more characterization information can be obtained through fewer test and analysis methods.

[0119] In another embodiment, the mean free path of the non-target layer of the sample is obtained by looking up a table, and then the relative thickness of the non-target layer is obtained by the second electron energy loss spectrum, and the relative mean free path of the target layer is calculated according to the mean free path and relative thickness of the non-target layer and the relative thickness of the target layer. When the mean free path of the non-target layer is relatively stable, the relative mean free path has a smaller error than the true mean free path, so that the mean free path of the target layer can also be obtained in samples that are not convenient to slice to obtain the true thickness.

[0120] The embodiments of the present application are described above, and these embodiments do not describe all the details in detail, nor do they limit the invention to the specific embodiments described. Obviously, many modifications and changes can be made based on the above description. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present application, so that those skilled in the art can make good use of the present application and the modifications based on the present application. The present application is only limited by the claims and their full scope and equivalents.

Claims

1. A method for characterizing a sample, wherein the sample comprises a target layer and at least one non-target layer, the target layer and the non-target layer are made of different materials, the surface of the sample is in a first direction, and the sample is a core structure in a 3D NAND large-scale integrated circuit, characterized in that: The characterization method of the sample includes: Performing electron energy loss spectrum analysis on the sample via the sample surface to obtain a first electron energy loss spectrum of the target layer and a second electron energy loss spectrum of the non-target layer; Obtaining the relative thickness of the sample target layer according to the zero-loss spectrum of the first electron energy loss spectrum; Obtaining the relative thickness of the non-target layer of the sample according to the zero-loss spectrum of the second electron energy loss spectrum; Obtaining the mean free path of the non-target layer by looking up a table; According to the relative thickness and mean free path of the non-target layer and the relative thickness of the target layer, the relative mean free path of the target layer is obtained. Among them, in the step of obtaining the relative mean free path of the target layer according to the relative thickness and mean free path of the non-target layer and the relative thickness of the target layer, when the actual thickness of the target layer and the non-target layer are the same, the calculation formula is: , represents the mean free path of the target layer, represents the mean free path of the non-target layer, Indicates the relative thickness of the non-target layer, Indicates the relative thickness of the target layer.

2. The characterization method according to claim 1, characterized in that The zero-loss spectrum of the first electron energy loss spectrum is: , Where I0 is the intensity of the zero peak in the first electron energy loss spectrum, I t It's full spectrum strength.

3. The characterization method according to claim 2, characterized in that In the step of obtaining the relative thickness of the sample target layer according to the zero-loss spectrum of the first electron energy loss spectrum, the relative thickness of the sample target layer is , Where t is the sample thickness and λ is the mean free path of the target layer of the sample.

4. The characterization method according to claim 1, characterized in that After the step of obtaining the relative mean free path of the target layer according to the relative thickness and mean free path of the non-target layer and the relative thickness of the target layer, the method further includes: Using a focused ion beam to slice the sample in a second or third direction to obtain the true thickness of the sample, wherein the second direction and the third direction are perpendicular to the first direction in pairs; The mean free path is calculated based on the relative thickness and true thickness of the target layer of the sample.

5. The characterization method according to claim 4, characterized in that: In the step of calculating the mean free path according to the relative thickness and the true thickness of the sample target layer, the mean free path of the sample target layer is: 。

Citation Information

Patent Citations

  • Detection method of semiconductor structure and detection device thereof

    CN114018760A

  • Method of determination of mean free path length of electrons

    SU1718069A1